Does biomass growth increase in the largest trees? Flaws, fallacies and alternative analyses. (14th November 2016) - Sheil, Douglas; Eastaugh, Chris S.; Vlam, Mart; Zuidema, Pieter A.; Groenendijk, Peter; van der Sleen, Peter; Jay, Alex; Vanclay, Jerome
Summary: The long‐standing view that biomass growth in trees typically follows a rise‐and‐fall unimodal pattern has been challenged by studies concluding that biomass growth increases with size even among the largest stems in both closed forests and in open competition‐free environments. We highlight challenges and pitfalls that influence such interpretations. The ability to observe and calibrate biomass change in large stems requires adequate data regarding these specific stems. Data checking and control procedures can bias estimates of biomass growth and generate false increases with stem size. It is important to distinguish aggregate and individual‐level trends: a failure to do so results in flawed interpretations. Our assessment of biomass growth in 706 tropical forest stems indicates that individual biomass growth patterns often plateau for extended periods, with no significant difference in the number of stems indicating positive and negative trends in all but one of the 14 species. Nonetheless, when comparing aggregate growth during the most recent five years, 13 out of our 14 species indicate that biomass growth increases with size even among the largest sizes. Thus, individual and aggregate patterns of biomass growth with size are distinct. Claims concerning general biomass growth patterns for large trees remain unconvincing. We suggest how future studies can improve our knowledge of growth patterns in and among large trees. A lay summary is available for this article. Abstract : Lay Summary